Inovasi Pengelolaan Talenta di Lembaga Pemerintahan dalam Meningkatkan Efektivitas Pelayanan Publik - Siska, Febria Marta (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Talent management in government institutions is a key factor in enhancing the effectiveness of public services in the digital era and modern bureaucracy. Innovations in talent management are increasingly essential to ensure that civil servants possess the skills, competencies, and capacities required to meet the dynamic demands of society. This study aims to analyze how innovations in talent management within government institutions can improve public service effectiveness. Using a qualitative approach based on a literature review and library research, this study examines various talent management models implemented in different countries, including human resource development strategies, merit-based systems, and the utilization of technology in public sector talent management. The findings indicate that competency-based talent management innovations, digital technology integration, and data-driven approaches significantly contribute to improving government workforce performance and public satisfaction with services. However, several key challenges hinder the implementation of these innovations, including resistance to change, limitations in digital infrastructure, and the lack of sustainable policy support. Therefore, a holistic and evidence-based talent management strategy is needed, supported by adaptive policies and technological advancements to enhance bureaucratic efficiency. This study provides insights for governments, policymakers, and academics in designing more innovative talent management strategies to strengthen professional, efficient, and citizen-oriented public services